Efektivitas Pembelajaran Daring pada Mata Pelajaran Sejarah di SMK Negeri 2 Sampit, Kabupaten Kotawaringin Timur - Amalia, Riza; Rahmawati, Novianti (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2021)
In Indonesia, the Covid-19 pandemic has transformed the learning process. Learning, which is generally performed offline (conventionally), must now be conducted online. This is performed to slow the spread of the Covid-19 virus. Sampit Vocational High School, one of the education providers in East Kotawaringin Regency, also offers online learning. The goal of this study was to obtain an overview of the effectiveness of online learning in history subjects at SMKN 2 Sampit. This study employs a qualitative approach with a descriptive method. Purposive sampling was used. There are a total of 12 subjects represented in the samples. In this study, data was gathered through an online survey created with Google Forms, as well as direct and online interviews conducted with the Zoom Cloud Meeting application. The Miles and Huberman model isÂ used in the data analysis technique. The study's conclusion is that the implementation of online learning in history subjects is declared effective, and it is described in three aspects: (1) aspects of the facilities and infrastructure owned by teachers for online learning, (2) aspects of student and teacher responses regarding the effectiveness of online learning in history subjects, and (3) aspects of student and teacher responses regarding the effectiveness of online learning in history subjects. (3) The final aspect is the use of online learning for history subjects to break the Covid-19 chain.